The wonder of the universe : hints of God in our fine-tuned world - Giberson, Karl. (Downers Grove, Illinois, IVP Books, 2012)
Like detectives sleuthing out the greatest mystery of all, scientists over the centuries have uncovered clues about the structure and origins of the universe. The work of Galileo, Newton, Einstein, and a host of other tenacious researchers and thinkers reveals a cosmos of almost unimaginable wonder and beauty. If we then honestly follow the evidence of science wherever it leads, where do we end up? Karl Giberson takes us on a fascinating guided tour of planets and protons, galaxies and gamma rays. We discover that if gravity were slightly stronger, neutrons a tiny bit lighter, the size of our sun somewhat larger or a dozen other factors altered by fractions, there would be no life. The author shows that for many observers, even those who do not embrace religious faith, all of this looks suspiciously like the expression of a grand plan -- a cosmic architecture capable of both supporting life such as ours, and inspiring observers like us to seek out hints of a creator. Join this cosmic expedition and discover the wonder of it all. - Publisher.
Introduction : Following the evidence where it leads -- Learning to read the book of nature : the beginning of science -- A wonderful world : science learns to walk -- Learning to see the universe : science learns to run -- The wonder of the cosmos : how the universe got a history -- Living on a Goldilocks planet : why the earth is such a great place to live -- Monkeying with the physics : the wonder of the world within the world -- Interlude : Crossing the uncertain bridge : can we get from science to religion? -- Is this the "best of all possible worlds"? : The design of design arguments -- Following the evidence : is there purpose in the universe? -- Cautious optimism : the real scoop on the fine-tuning of the universe -- It's a wonderful world.
Includes bibliographical references and index.
Keywords: Religion and science